2018
DOI: 10.3389/fimmu.2018.00681
|View full text |Cite
|
Sign up to set email alerts
|

Robust Humoral and Cellular Immune Responses to Pertussis in Adults After a First Acellular Booster Vaccination

Abstract: IntroductionTo reduce the pertussis disease burden, nowadays several countries recommend acellular pertussis (aP) booster vaccinations for adults. We aimed to evaluate the immunogenicity of a first adult aP booster vaccination at childbearing age.MethodsIn 2014, healthy adults aged 25–29 years (n = 105), vaccinated during infancy with four doses of whole-cell pertussis (wP) vaccine, received a Tdap (tetanus, diphtheria, and aP) booster vaccination. Blood samples were collected longitudinally pre-booster, 2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 47 publications
(51 reference statements)
1
28
0
Order By: Relevance
“…However, only a high country-wide coverage of these boosters might have a significant influence on the pertussis incidence. Moreover, there is evidence that the immunogenicity of repeated aP boosters seems to diminish, although the persistence of aP vaccine-induced antibodies after a first booster in wP-primed adults appeared to be longer compared to children 25 . Furthermore, many studies have shown the kinetics of anti-PT IgG antibodies and how they quite rapidly wane after vaccination or even after infection, although more prolonged 26 28 .…”
Section: Discussionmentioning
confidence: 99%
“…However, only a high country-wide coverage of these boosters might have a significant influence on the pertussis incidence. Moreover, there is evidence that the immunogenicity of repeated aP boosters seems to diminish, although the persistence of aP vaccine-induced antibodies after a first booster in wP-primed adults appeared to be longer compared to children 25 . Furthermore, many studies have shown the kinetics of anti-PT IgG antibodies and how they quite rapidly wane after vaccination or even after infection, although more prolonged 26 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, stronger IL-17 polarization from wP vaccination has been reported to be associated with higher protection in baboon models (15,26,27,44) and to be pivotal in the mediation of adaptive immunity by tissue-resident memory T cells after natural infection in mice (45,66). Although IL-17 has been detected in supernatants of PBMCs stimulated with pertussis antigens (67,68), to the best of our knowledge, this is the first time that CD4 + T cells secreting both IL-9 and IL-17 have been shown to be associated with pertussis-specific responses after wP or aP vaccination regimens in humans.…”
Section: Discussionmentioning
confidence: 99%
“…No correlate of protection has been defined for pertussis ; however, high antibody levels are important . Several papers have used arbitrary thresholds when analysing pertussis antibody levels , and thus for our analysis we utilised the commonly used arbitrary threshold of ≥20 IU/ml for PTx, FHA and Prn antibody concentrations. A significantly higher percentage of infants from vaccinated pregnancies reached these antibody levels for tetanus and diphtheria, and the arbitrarily defined threshold for pertussis antibody in the first 7 weeks of life, compared to infants born from unvaccinated mothers.…”
Section: Discussionmentioning
confidence: 99%